First Molecular Identification and Diversity of Endophytic Fungi from Native Plants in the Cyrene Region, Libya - Salma O. Jadallah; Najat Salem Emhamed; Abdlmanam Fakron (African Journal of Advanced Pure and Applied Sciences, 2026)
Endophytic fungi live inside plant tissues without causing symptoms. They play important roles in boosting host growth and helping plants handle stress. This study is the first Molecular Identification endophytic fungi from native plants in the Cyrene region of Libya at the molecular level. We collected 68 fungal isolates from six plant species after thorough surface sterilization. We selected six representative isolates for molecular analysis based on their physical differences. We amplified and sequenced the Internal Transcribed Spacer (ITS) region of the ribosomal DNA for identification. The identified fungi and their GenBank accession numbers are as follows: Aspergillus niger (PQ178951), Fusarium sp. (PQ178952), Penicillium nagliovense (PQ178953), Fusarium chlamydosporum (PQ178954), Penicillium chrysogenum (PQ178955), and Stagonosporopsis lupini (PQ182696). BLASTn analysis indicated 99-100% sequence similarity to reference strains. The presence of genera like Fusarium and Penicillium suggests strong ecological adaptation. This study provides essential DNA barcode data for fungal endophytes in this unexplored region. The results highlight the region's rich fungal diversity and suggest that these isolates could be useful for future biotechnological research, such as the production of bioactive compounds for industrial and pharmaceutical uses.